VAKSINASI INDUK LELE DUMBO (Clarias gariepinus) UNTUK MENINGKATKAN KELULUSHIDUPAN DAN PERTUMBUHAN PADA TAHAP PENDEDERAN - Triyanto Triyanto; Kamiso H. N.; A. Isnansetyo (Universitas Gadjah Mada, 1996)
Female and male brooders were vaccinated by intraperitoneal injection and intramuscular injection respectively. Unvaccinated brooders were used as control. Fry which was produced by vaccinated and unvaccinated brooders were reared separately in paddy field pond for 15 days for the first nursery rearing period and another 15 days for the second nursery rearing period. These field experiment conducted in four locations, namely slmean (2 location) and magelang (2 location). Results of these experiments indicated that brooders vaccination could increase survival rates of the first and the second nursery rearing periods approximately 65.00% and 3.69% respectively. Average weight and total length of fry which produced by vaccinated broodstock increased 12.59% and 58.51% during the first nursey rearing period, 8.55% and 7.14% during the second nursery period.